Advances in the determination of the mechanical properties of thin membranes through dynamic tests - Lima-Rodríguez, Antonia María; Caminos-Gámez, Luis Francisco; González-Herrera, Antonio; García-Manrique-Ocaña, José Manuel (Universidad de Málaga, 2023)
The mechanical properties of thin membranes can be determined by non-destructive dynamic tests. When a membrane is subjected to sound pressure, it vibrates according to its natural modes. These vibration modes depend directly on their mechanical characteristics, including Young's modulus. The interaction between sound waves and the membrane (mechanical-acoustic coupling) is complex and requires a thorough study: For this reason, it is necessary to evaluate different aspects that influence in the natural frequencies present in the response. Among these parameters are: the position of the sound source, the measurement points, the geometry and dimensions of the material, the frequency range or the quantities to be measured, among others. This work presents the first results of a new case study with more data of excited frequencies and measurement points, to improve the precision of the results obtained.
El editor de las actas del Congreso da permiso para poner el texto completo en el repositorio institucional de la uma.
Keywords: Membranas (Tecnología) - Congresos; Mechanical properties; Membrane; Dynamic test; Natural frequencies; Sound source